2022
DOI: 10.1172/jci.insight.157597
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody targeting the conserved region of the SARS-CoV-2 spike protein to overcome viral variants

Abstract: Most therapeutic monoclonal antibodies target the receptor-binding domain (RBD) of the spike protein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Unfortunately, the RBD is a hot spot for mutations in SARS-CoV-2 variants, which will lead to loss of the neutralizing function of current therapeutic monoclonal antibodies. Universal monoclonal antibodies for different variants are necessary. We identified monoclonal antibodies that recognized the S2 region of the spike protein, which is ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…Syrian hamsters (n = 5–6 per group) were challenged intranasally with 1 × 10 5 TCID 50 (WA1, D614G, and Alpha), or 1 × 10 3 TCID 50 (Delta) SARS-CoV-2 in 50 μl under isoflurane anesthesia. After 3 h, each hamster was injected with 1 mg or 5 mg of mAb-S5[ 30 ]. Half-hamsters in each group were sacrificed at Day 3 after challenge to quantify the viral load.…”
Section: Methodsmentioning
confidence: 99%
“…Syrian hamsters (n = 5–6 per group) were challenged intranasally with 1 × 10 5 TCID 50 (WA1, D614G, and Alpha), or 1 × 10 3 TCID 50 (Delta) SARS-CoV-2 in 50 μl under isoflurane anesthesia. After 3 h, each hamster was injected with 1 mg or 5 mg of mAb-S5[ 30 ]. Half-hamsters in each group were sacrificed at Day 3 after challenge to quantify the viral load.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, Ladner et al generated an epitope-resolved analysis of IgG cross-reactivity among all CoVs in COVID-19-negative and recovered patients using a highly multiplexed peptide assay (PepSeq) and discovered that the epitopes at the FP, which is 93% similar among strains of betacoronaviruses and alphacoronaviruses, produced broadly neutralizing antibodies against the endemic coronaviruses, including SARS-CoV, MERS-CoV and SARS-CoV-2 [ 41 , 125 ]. Likewise, the HR2 region of the S2 is 100% conserved among the variants of the SARS-CoV-2 [ 41 , 128 ]. The S2 subunit proteins could also induce cross-reactive antibodies against the SARS-CoV SP and the endemic CoVs [ 130 ].…”
Section: Sars-cov-2 S Conserved Regions As a Potential Target For Vac...mentioning
confidence: 99%
“…Interestingly, Ladner et al generated an epitope-resolved analysis of IgG cross-reactivity among all CoVs in COVID-19-negative and recovered patients using a highly multiplexed peptide assay (PepSeq) and discovered that the epitopes at the FP which is 93% similar among strains of betacoronaviruses and alphacoronaviruses produced broadly neutralizing antibodies against the endemic coronaviruses including SARS-CoV, MERS-CoV, and SARS-CoV-2 [41,110]. Likewise, the HR2 region of the S2 is 100% conserved among the variants of the SARS-CoV-2 [41,111]. The S2 subunit proteins could also induce cross-reactive antibodies against the SP SARS-CoV and the endemic CoVs [81].…”
Section: Sars-cov-2 S Conserved Regions As a Potential Target For Vac...mentioning
confidence: 99%
“…In a recent publication, Wu et al identified a monoclonal antibody hMab5.17 that could recognize the SARS-CoV-2 HR2 domain that is adjacent to TM (SPDVDLGDISGINAS; 1161-1175 aa) and could protect against SARS-CoV-2 in the Syrian hamster. They further cloned the mAb hMab5.17 and demonstrated that it could neutralize SARS-CoV-2 variants [111].…”
Section: Sars-cov-2 S Conserved Regions As a Potential Target For Vac...mentioning
confidence: 99%